Sulphur-containing derivatives structurally related to fenoxycarb are potent growth inhibitors against the intracellular form of Trypanosoma cruzi - Rodriguez, Juan Bautista (2000)
Sulphur-containing derivatives structurally related to the insect growth regulator fenoxycarb were shown to be extremely active antiproliferative agents against the amastigote form of Trypanosoma cruzi in in vitro assays. All of these drugs had previously been proved to be remarkably potent growth inhibitors against the epimastigote form of the parasite.